2015
DOI: 10.18410/jebmh/2015/1099
|View full text |Cite
|
Sign up to set email alerts
|

A Study on Outcome of Cortical Mastoidectomy With Tympanoplasty in Csom

Abstract: To perform tympanoplasty with mastoidectomy in chronic supporative otitis media cases. To periodically evaluate the post operative benefit in terms of graft take up and hearing improvement. METHODS: A prospective study where 42 patients with CSOM underwent tympanoplasty with cortical mastoidectomy in department of ENT at Katuri Medical College and Hospital. Underlay technique with temporalis fascia graft, cortical mastoidectomy was done in all cases. Follow up at 3 months, 6 months and 1year was done for graft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 2 publications
0
0
0
Order By: Relevance
“…In our study we did not find a significant association between active or inactive state of mucosal disease and antral status. Previous studies have different views regarding mastoid exploration in wet ears (6)(7)(8)(9)(10)(11). Palukri et al has suggested that mastoid must be explored in wet ears to clear pathology in antrum (6).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study we did not find a significant association between active or inactive state of mucosal disease and antral status. Previous studies have different views regarding mastoid exploration in wet ears (6)(7)(8)(9)(10)(11). Palukri et al has suggested that mastoid must be explored in wet ears to clear pathology in antrum (6).…”
Section: Resultsmentioning
confidence: 99%
“…Mastoid exploration can be done in form of a cortical mastoidectomy or a limited antrostomy. "Cortical mastoidectomy is a surgical procedure done to remove disease from the mastoid antrum, mastoid air cell system and aditus with preservation of intact bony external auditory canal wall, without disturbing the existing middle ear contents" (6).…”
Section: Introductionmentioning
confidence: 99%